Regulating the redox centers of Fe through the enrichment of Mo moiety for persulfate activation: A new strategy to achieve maximum persulfate utilization efficiency - Ali, Jawad; Wenli, Lei; Shahzad, Ajmal; Ifthikar, Jerosha; Aregay, Gebremedhin G.; Shahib, Irshad Ibran; Elkhlifi, Zouhair; Chen, Zhulei; Chen, Zhuqi (Water research (Oxford), 2020)
Persulfate Fe-based catalytic oxidation is considered as one of the most attractive strategy for the growing concerns of water pollution. However, the undesirable FeIII/FeII redox cycle restrict them from attending the sustainable activity during practical applications. This study was intended to develop a new strategy to regulate the redox cycles of FeIII/FeII by introducing the second redox center of MoS42− in the interlayers of Fe-based layered double hydroxide (FeMgAl–MoS4 LDH). Based on the first-order kinetic model, the fabricated FeMgAl–MoS4 catalyst was 10–100 fold more reactive than the bench marked peroxymonosulfate (PMS) activators including FeMgAl LDHs and other widely reported nano-catalysts such as Co3O4, Fe3O4, α-MnO2, CuO–Fe3O4 and Fe3O4. The enhanced catalytic activity of FeMgAl–MoS4 LDH was related to the continuous regeneration of active sites (FeII/MoIV), excellent PMS utilization efficiency and generation of abundant free radicals. Moreover, the FeMgAl–MoS4/PMS system shows an effective pH range from 3.0 to 7.0 and the degradation kinetics of parahydroxy benzoic acid (PHB) were not effected in the presence of huge amount of background electrolytes and natural organic matters. Based on the in-situ electron paramagnetic resonance spectroscopy (EPR), chemical scavengers, XPS analysis and gas chromatography couple with mass spectrometer (GC-MS), a degradation pathway based on dominant free radicals (•SO4− and •OH), passing through the redox cycles of FeIII/FeII and MoVI/MoIV was proposed for PMS activation. We believe that this strategy of regulating the redox center through MoS42− not only provides a base to prepare new materials with stable catalytic activity but also broaden the scope of Fe-based material for real application of contaminated water. [Display omitted] •Intercalated MoS42− is essential to control the FeIII/FeII redox cycles.•FeMgAl–MoS4 catalyst was 10–100 fold more reactive than most PMS activators.•Excellent PMS utilization resulted from the continuous circulation of redox metals centers.•Consistent performance could be maintained under various water parameters.